Phytoplankton Abundance and Distribution Chloropyll-a in Reservoir - Syahnan Aly Lubis; Niken Tunjung Murti Pratiwi; Hefni Effendi (Depik, 2024)
Organic matter entering through the inlet and activities in the Koto Panjang Reservoir body is feared to be the main source of nutrient contribution in the form of nitrogen (N) and phosphate (P) for reservoir waters. Nutrients N and P are utilised by phytoplankton in the photosynthesis process. If this condition continues, it is feared that it will affect water quality (blooming algae) which has an impact on aquatic biota. This study aims to determine the type and abundance of phytoplankton along with the distribution of chlorophyll a in reservoir waters. This study used descriptive, qualitative and quantitative methods and analysed the distribution of chlorophyll a using surfer software. Based on the results of the study, it is known that water quality is relatively good with temperatures ranging from 26-310C, brightness ranging from 0.69-1.96 m, dissolved oxygen (DO) is 5.60-6.80 mg/L and turbidity is 1-6 NTU. The results showed that phytoplankton composition was composed of 5 classes consisting of Euglenophyceae (1 species), Cyanophyceae (3 species), Conjugatophyceae or Zygnematophyceae (4 species), Chlorophyceae (4 species) and Bacillariophyceae (10 species). The dominating class in the reservoir zonation is different. In the riverine zone the Bacillariophyceae class dominates by 60.06%, in the transition zone the Cyanophyceae class by 91.60% and in the lacustrine zone the dominating class is Conjugatophyceae or Zygnematophyceae by 78.69%. Phytoplankton abundance ranged from 166.5-2,193 sell/m3. The highest abundance was located in the lacustrine zone and the lowest abundance in the riverine zone. The distribution of chlorophyll a in Koto Panjang Reservoir is varied, the highest distribution is located in the transition zone to the lacustrine zone.